Andrzej Szczypiorski – z biografii pisarza i publicysty - Worsowicz, Monika (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2003)
Andrzej Szczypiorski (1928–2000) was a writer and journalist. As a journalist he made his debut in 1947 in “Gromada” and then he cooperated with “Życie Warszawy” and “Film". In 1951 he was a member of literary editor’s office of Polish Radio in Katowice, where he was engaged in reportage and radio’s adaptations of literary works. After short period of work in Teatr Śląski in Katowice and departure to embassy in Copenhagen (Denmark) he arrived to Warsaw and he engaged in cultural journalism. Every week’s feuilletons-commentary in radio and numerous texts printed for example in “Przegląd Kulturalny”, “Życie Warszawy". “Za wolność i lud”, “Nowa Kultura”, “Tygodnik Demokratyczny”, “Tygodnik Kulturalny” made him famous journalist. He was reckoned to be a journalist, who supported obligatory political system. Since 1968 his connections with radio and official press have started to come loose. After next few years he cooperated to “Polityka”, “Odra”, “Problemy Alkoholizmu” and “Literatura". Formation independent press made him publicity in “Zapis”, “Biuletyn Informacyjny", "Bez tytułu" . During being internee in the state of war he became concentrated on literary activity. In 1989–1991 years he was a senator. Till his death he published very much (e.g. “Gazeta Wyborcza”, “Wprost”, “Polityka” and “Hustler”) and he took part in television and radio programs, symposiums and cultural meeting in the country and foreign countries.